Implementasi Pembuatan Peta Digital Wilayah Pedagang dan QRIS sebagai Strategi Pemberdayaan Ekonomi Masyarakat Kelurahan Aek Kota Batu - Nessa Anggi Sahputri; Nurul Rizkia Hasibuan; Nursinta Ritonga; Sri Pujiyama Pasaribu; Iwan Nasution (Jurnal Pengabdian Masyarakat Waradin, 2026)
The Community Service Program (KKN) of the Faculty of Islamic Economics and Business, State Islamic University of North Sumatra, in Aek Kota Batu Village, North Labuhanbatu Regency, was carried out as a form of community service focusing on digital-based economic empowerment. This program originated from the low level of digital literacy and the limited ability of micro-entrepreneurs to utilize technology as a means of promotion and financial transactions. The main objective of this activity is to enhance the community’s ability to use digital maps and the QRIS (Quick Response Code Indonesian Standard) payment system as a strategy to expand market reach and create transaction efficiency. The method used is the Participatory Rural Appraisal approach, with stages including observation, socialization, training, mentoring, and evaluation. The results of the activity show that the community experienced an increased understanding of digital technology and was able to apply digital mapping to ten local business units. In addition, several business actors have implemented QRIS in daily transactions, which has proven to improve convenience and security in financial dealings. From the perspective of Islamic economics, this activity represents the values of maslahah (public benefit), itqan (excellence), and tawazun (balance) in the community’s economic life. Thus, this program successfully created a socio-economic transformation based on Islamic values and can serve as a model for digital economy-based community service programs at the village level.